THE INFLUENCE OF ILLUSION OF CONTROL BIAS, OVERCONFIDENCE, HERDING AND REPRESENTATIVE ON STOCK INVESTMENT DECISION MAKING IN PONTIANAK CITY INVESTORS - Desya Prasasni; Dedi Hariyanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the influence of Illusion of control bias, overconfidence, Herding and Representative on stock investment decision making among investors in Pontianak City. The sampling technique used in this research was the Purposive Sampling technique. The population in this study amounted to 150 respondents. The analytical tools used in this research are instrument tests consisting of validity and reliability tests, for classical assumption tests consisting of normality tests, linearity tests and multicollinearity tests, then for statistical analysis consisting of multiple linear regression analysis, correlation coefficient (R) analysis. , analysis of the coefficient of determination (R2), simultaneous influence test (F statistical test), partial influence test (t statistical test). The validity test results show that the data is valid, the reliability test results show that the data is reliable. Then the results of the normality test show that the data is normally distributed, the results of the linearity test show that the model used has a linear relationship, and the results of the multicollinearity test show that there is no multicollinearity in this study. Based on the results of multiple linear regression analysis, Y = 2.288 + 0.350X1 + 0.312X2 + 0.408X3 + 0.016X4 + e is 0.370, meaning that the variables illusion of control bias, overconfidence, herding, representativeness and stock investment decision making have a weak relationship. Analysis of the coefficient of determination (R2) is 0.137, meaning that illusion of control bias, overconfidence, herding and representativeness have an influence of 13.7% on stock investment decision making, while the remaining 86.3% is influenced by other variables. Simultaneous test results (F test) illusion of control bias, overconfidence, herding and representation simultaneously influence stock investment decision making. The results of the illusion of control bias t test partially have no significant effect on stock investment decision making for investors, partial overconfidence has a significant effect on stock investment decision making for investors, partial herding has a significant effect on stock investment decision making for investors, and partial representativeness does not have a significant effect on stock investment decision making among Pontianak City investors.